PERUBAHAN SUDUT POLARISASI ALAMI DAN ELEKTROOPTIS MINYAK SAWIT YANG DICAMPUR BERBAGAI MINYAK HEWANI - Idrus, Hadiyati; Kaltsum, Ummi; Firdausi, K. Sofjan (Sainstek : Jurnal Sains dan Teknologi, 2017)
Palm oil-based cooking oil is the most widely used cooking oil. Palm oil circulating in the market is often mixed with animal oil by culinary entrepreneurs with a view to produce a more tasty taste so it needs to be examined purity. Research on the content of saturated fatty acids using gas chromatography mass spectrophotometer (GCMS) requires quite expensive cost so that an alternative method is needed to determine the quality of cooking oil; especially its purity is by using polarization both naturally and by electrooptic method. This research uses incandescent lamp as light source. Samples flanked by parallel metal plates are placed between polarizers and analyzers. Samples of a mixture of palm oil with each animal oil (chicken oil, pork oil, cow oil). The samples of each oil are tested byu using natural polarization (active polarization) and electro-polarization polarization (impact polarization). The results showed that the polarization angle change in the oil of the mixture was greater than that of pure palm oil with the greatest angular change produced by a mixture of palm oil and cow oil (1.5 for natural polarization and 3 for electro-polarization). This result was in accordance with the result of the titration test shows that mixed oils have free fatty acids and PV peroxide numbers higher than pure palm oil. The cow's oil mix is the greatest change compared to pigs and chickens. This result shows that cow's oil has the highest saturated fatty acid content. Electrooptical polarization angle larger than natural polarization. This is due to the interaction of the electric field of the light source with the electric field of the molecule induced by the electric field of the power supply. The polarization method successfully distinguishes the type of pure and mixed cooking oil.